Бөмбөгөрийн бичээс - Баттулга, Ц. (Acta Mongolica, 2005)
A new monument with runic inscription and stamps has been found in the heap of the hill named Shiveet, the end of Tain mountains, in the south west, at 11 km distance for from Bumbugur soum, Bayankhonggor province.